Implementation of Paok Pampang Village Regulation No. 03 of 2021 concerning the Prevention of Child Marriage - Madani Putri; Rispawati Rispawati; M. Samsul Hadi (JURNAL PENDIDIKAN IPS, 2025)
Child marriage remains a significant social problem affecting the health, education, and future of the younger generation, including in Paok Pampang Village. To address this, the village government issued Village Regulation Number 03 of 2021 on the Prevention of Child Marriage. This research aims to examine the implementation of the regulation and the factors influencing it. Using a qualitative approach with an empirical juridical method, data were obtained through interviews, observation, and documentation. Findings show that the implementation has been gradual yet has contributed positively to reducing child marriage rates between 2019 and 2024. Key programs include community outreach, promoting marriage at a mature age, reproductive health education, and the establishment of Youth Integrated Health Posts (Posyandu Remaja) and the Child Protection Task Force. These initiatives reflect the integration of legal structure, substance, and culture, as described in Lawrence M. Friedman’s legal system theory. Supporting factors include strong coordination between village authorities and community leaders, relevant regulatory content, and growing public legal awareness. Meanwhile, challenges involve low economic conditions, peer influence, limited implementing personnel, and the impact of labor migration abroad. Overall, the regulation’s implementation is considered fairly effective, though it requires institutional strengthening and broader community participation to ensure sustainable outcomes.